Hubungan Antara Anemia dan Kebiasaan Merokok pada Ibu Hamil dengan Kejadian BBLR di Rumah Sakit Umum Pusat Dr. Mohammad Hoesin Palembang Tahun 2016 - sari, Intan (Sriwijaya Journal of Medicine, 2018)
Low Birth Weight (LBW) is an infant born with a birth weight of less than 2500 grams regardless of gestation. Birth weight is the weight of the baby weighed in 1 hour after birth. (Depkes RI, 2009). Based on WHO and UNICEF data, in 2013 about 222 million babies were born in the world, of which 16% were born with low birth weight. The percentage of LBW in developing countries is 16.5% twice that of developed countries (7%) (Scholar Unand, 2014). The purpose of this study was to determine whether there is a relationship between anemia and Smoking Habit in Pregnant Women with LBW occurrence in General Hospital Dr. Mohammad Hoesin Palembang Year 2016. This research use analytical survey method with cross sectional approach. The population in this study were all mothers who gave birth monthly in Midwifery Installation of Dr. General Hospital Mohammad Hoesin Palembang in 2016 as many as 315 respondents. The sample of this research is some of mothers who give birth enough month in Midwifery Installation of Dr. General Hospital Mohammad Hoesin Palembang Year 2016 as many as 315 respondents. ". From the results of bivariate analysis of anemic respondents with the occurrence of LBW obtained statistical test X2 count = 23.22 which means there is a significant relationship between anemia with the incidence of BBLR. Respondents smoking with the occurrence of LBWR obtained statistical test X2 count = 41.20 which means there is a relationship Meaningful between smoking and LBW incidence. From the results of this study is expected that this research can be a reference material and is a complete information and useful for the development of knowledge about LBW.